Steam flaking conditions and gelatinization in sorghum grain - Roth, G.M.; Brent, B.E.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Gelatinization was measured in flaked sorghum grain that weighed 16.5 to 47 lbs. a bushel. Samples were steamed from 20 to 50 minutes, and varied in moisture content from 16.9 to 20.9% as they entered the chamber. Gelatinization was measured by an enzymatic gas production technique and compare with an extruded sample assumed to be 100% gelatinized. Each 1 lb. a bushel decrease in weight between 16.5 and 38 lbs. increased gelatinization 3.65 percent. Each 10 min. increase in steaming time increased gelatinization only 1.5%. Changes in grain moisture between 16.9 and 20.9% only slightly influenced gelatinization percentage. Between 20 and 28 lbs./bu., each pound decrease in bushel weight decreased the capacity of the 18” x 24” Ross roller mill 9 lbs. per minute.
Keywords: Beef; Gelatinization; Sorghum grain; Steam flaking